2015
DOI: 10.1097/aci.0000000000000179
|View full text |Cite
|
Sign up to set email alerts
|

Diet and asthma

Abstract: Purpose of review Our objective is to provide an overview and discussion of recent experimental studies, epidemiologic studies, and clinical trials of diet and asthma. We focus on dietary sources and vitamins with antioxidant properties (vitamins (A, C, and E), folate, and omega-3 and omega-6 polyunsaturated fatty acids (n-3 and n-6 PUFAs). Recent findings Current evidence does not support the use of vitamin A, vitamin C, vitamin E or PUFAs for the prevention or treatment of asthma or allergies. Current guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 51 publications
0
37
0
1
Order By: Relevance
“…Temporal changes in dietary patterns and obesity may partly explain the asthma epidemic in industrialized countries . Whereas a Western diet (rich in proinflammatory foods and poor in antioxidant foods) has been linked to asthma incidence and prevalence, an “anti‐inflammatory diet” has been associated with decreased asthma symptoms .…”
Section: Discussionmentioning
confidence: 99%
“…Temporal changes in dietary patterns and obesity may partly explain the asthma epidemic in industrialized countries . Whereas a Western diet (rich in proinflammatory foods and poor in antioxidant foods) has been linked to asthma incidence and prevalence, an “anti‐inflammatory diet” has been associated with decreased asthma symptoms .…”
Section: Discussionmentioning
confidence: 99%
“…Airway and systemic inflammation as well as oxidative stress are recognized mechanisms involved in the pathogenesis of asthma and allergic diseases . Antioxidants reduce reactive oxygen species (ROS) and epidemiological studies have reported inverse associations between diets rich in antioxidants and allergic diseases; however, results are inconsistent and previous studies on school age intake have often been cross‐sectional .…”
Section: Introductionmentioning
confidence: 99%
“…A variety of antioxidant supplements and nutrients has been studied for the treatment of asthma. 16,47 A few studies have shown the beneficial effect of antioxidants on pulmonary functions and on asthmatic symptoms. 17,18 In our study, we studied the relationships between oxida-tive stress markers and either vitamins in serum or the daily intake of vitamins over a very short period, and no relationships were found.…”
Section: Discussionmentioning
confidence: 99%